Correlation between Development of Ethical Behavior and its Consequences in Workplace Environment, and Organizational Health: developments of managers’ ethical behavior with organizational health - Zameni , Farshideh (Bioethics and Health Law Journal (BHL), 2021)
Background and Aim: This research has been done to determine the correlation between the development of ethical behavior and its consequences in a workplace environment, and the health of an organization. Materials and Methods: This research is theoretically correlative descriptive and benefits a practical purpose. The research population included 5083 people from the staff of Azad and state universities in Mazandaran, among them, based on Kerjecy and Morgan table via simple random sampling 346 people were selected as the sample of research. The instruments included two questionnaires, standard health of organization questionnaire with 21 questions, and a researcher-made questionnaire of development of ethical behavior in a workplace environment with 35 questions which by applying the preliminary design on a sample of 30 people the reliability was reported 0.94. The data were analyzed descriptively and inferentially by using mean, standard deviation, Pearson correlation coefficient, fisher, and Regression statistics. Ethical Considerations: Before the distribution of the questionnaires, the objectives and method of implementation of the study were explained to the participants. In addition, written informed consents were obtained from the subjects before the study, and they were assured of the confidentiality terms regarding their personal information. The participants were also allowed to withdraw from the study at any time. Findings: The results show a linear relationship between teaching ethical principles, selection of the staff with ethical potentiality, propagation of ethical rules and codes, degree of managers’ commitment to ethical standards, and eventually the development of ethical behavior and the health of the organization. Conclusion: Considering the results and to have a healthy organization founded on a healthy basis it is recommended that officials and authorities at high levels of the organizational hierarchy have a special attitude towards selecting managers with good ethical manners, and diligently try to adopt policies to draft an ethical charter in the organization. *Corresponding Author: Farshideh Zameni; Email: f_zameni@yahoo.com; ORCID: https://orcid.org/0000-0001-9228-3527 Please cite this article as: Zameni F. Correlation between Development of Ethical Behavior and its Consequences in Workplace Environment, and Organizational Health. Bioeth Health Law J. 2021; 1:1-4 (e22). http://doi.org/10.22037/bhl.v1i1.38183